The peculiarities of reproductive biology of some rare Rhododendron spesies in the conditions of North Bukovyna - Vanzar, O.N.; Vanzar, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The modern state of some rare Rhododendron species is analysed and causes of decrease of their quantity are established. The results of introduction of rare Rhododendron species in North Bukovyna are presented. Their reproductive abilities are investigated. Absence of anomaly in generative development of rare Rhododendron species is marked. Ornamental rare species of Rhododendron are recommended for dendroflora of North Bukovyna.